The Problem of Idleness: An Arendtian Justification of Universal Basic Income in the Face of Mass Automation - Lewicki, James (Université d'Ottawa / University of Ottawa, 2019)
This dissertation is concerned with a fundamental problem at the heart of Arendt’s The Human Condition—namely, ‘the problem of idleness’. This problem is related to the three types of human Arendt identifies as correlated to dominant activities in one’s life, animal laborans, homo faber, and the acting person. It explores Arendt’s predictions of an oncoming automation crisis, and the possibility of a corresponding crisis in the production—consumption cycle. The problem of idleness can be understood as the claim that if people are provided freedom from job-holding so that they may pursue other activities, they would likely turn to consumption to occupy their time. I claim that this problem of idleness is important in any consideration of an oncoming automation crisis, especially in relation to Universal Basic Income (UBI) as a solution to such a crisis. I claim that there is a hole in the UBI literature concerning this problem of idleness, and if left unaddressed it would result in both an ineffective UBI, and in a crisis of meaning for the general populace. This dissertation demonstrates what the problem of idleness is, why it is important, and what possible solutions exist. This contributes to the UBI literature by diagnosing and attempting to solve a gap in the literature which I argue would cause practical challenges in the implementation and stability of a UBI system. I also contribute to the Arendtian literature by problematizing traditional readings of Arendt, and offering a reappraisal of her thought on Marx, art, and the social.
Keywords: Universal Basic Income; Hannah Arendt; Karl Marx; Social; Art; Automation; Postwork; Antiwork; Sara Ahmed; Phenomenology; The Human Condition; On Revolution; job-holding; Welfare